2014
DOI: 10.1159/000367583
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Invasive Micropapillary Carcinoma with Intestinal Phenotypes Harboring a TP53 R175H Mutation

Abstract: We report a case of gastric invasive micropapillary carcinoma (IMPC) in an 86-year-old female patient. She was admitted to our hospital with a chief complaint of bloody emesis. Upper gastrointestinal endoscopy found a gastric adenocarcinoma at the antrum. The biopsy specimens showed moderately differentiated adenocarcinoma with invasive small tumor nests. Distal gastrectomy with systematic lymph node dissection demonstrated that the tumor had IMPC through a pathological examination. Despite the depth of tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…We observed that the same mutations were present in both the initial and recurrent samples (Figure 4). The TP53:p.R175H mutation is a functional acquired mutation closely related to the high invasiveness and metastatic potential of many cancers 20 . TP53:p.R273C is also a functional acquired mutation that promotes the proliferation, invasion, and drug resistance of tumor cells 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the same mutations were present in both the initial and recurrent samples (Figure 4). The TP53:p.R175H mutation is a functional acquired mutation closely related to the high invasiveness and metastatic potential of many cancers 20 . TP53:p.R273C is also a functional acquired mutation that promotes the proliferation, invasion, and drug resistance of tumor cells 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The TP53:p.R175H mutation is a functional acquired mutation closely related to the high invasiveness and metastatic potential of many cancers. 20 TP53:p.R273C is also a functional acquired mutation that promotes the proliferation, invasion, and drug resistance of tumor cells. 21 The 1p/19q co‐deletion is positively associated with IDH mutations, while it is mutually exclusive with ATRX loss and TP53 mutation, which are the hallmarks of diffuse astrocytoma.…”
Section: Resultsmentioning
confidence: 99%
“…PBAM results for stomach adenocarcinoma can be found in Figure 16 . We identified that mutations in ARID1A, LRP1B, and TP53 [172] , [173] formed three major parent nodes. Mutation in ARID1A appears to be causal to chains of alterations within the same gene.…”
Section: Resultsmentioning
confidence: 99%